Er doped layered perovskites with dual mode luminescent behavior and tunable multicolor upconversion emission. (19th February 2019) - Khodabakhsh, Mohammadreza; Unal, Ugur
Abstract: Er 3+ doped BST nanoparticles with Aurivillius layered structure are synthesized through common solid-state method. Photoluminescence spectroscopy has shown that these oxides are capable of emitting light under UV (366 nm) and IR (980 nm) source. The effect of Er 3+ to Yb 3+ concentration ratio on upconversion emission are investigated and possible upconversion and energy transfer mechanisms are suggested based on the number of photons participating in UC process. Shift in the upconversion emission from green to red region is visualized by CIE chromaticity diagram. The superiority of coexistence of stoke and anti-stoke emission in a single host lattice with a single activator ion, besides to tunability of UC luminescence only by controlling sensitizer/activator ratio are very interesting features which can be used to produce dual mode multicolor luminescent ink with high security level against forgery.